Development of reading skills and writers to students pursuing or wake and overall cycle: a major challenge support - Gloria Orozco de Barros; Diana Linero L.; Rebeca Gonzalez S.; Zuany Paba A.; Martiniano Acosta A.; Alberto Prado M.; Rocio Argote R. (Universidad del Magdalena, 2014)
Magdalena University along its 40 years of existence had not considered it necessary to include in their curricula reading, writing and orality, because it was understood that who entered Higher Education was prepared enough in these issues and could apply properly for study and access to knowledge.